An Examination of Brain Abnormalities and Mobility in Individuals with Mild Cognitive Impairment and Alzheimer's Disease - Fischer, Barbara L.; Bacher, Rhonda; Bendlin, Barbara B.; Birdsill, Alex C.; Ly, Martina; Hoscheidt, Siobhan M.; Chappell, Richard J.; Mahoney, Jane E.; Gleason, Carey E. (Frontiers in Aging Neuroscience, 2017)
BACKGROUND: Mobility changes are concerning for elderly patients with cognitive decline. Given frail older individuals’ vulnerability to injury, it is critical to identify contributors to limited mobility. OBJECTIVE: To examine whether structural brain abnormalities, including reduced gray matter volume and white matter hyperintensities, would be associated with limited mobility among individuals with cognitive impairment, and to determine whether cognitive impairment would mediate this relationship. METHODS: Thirty- four elderly individuals with mild cognitive impairment and Alzheimer’s disease underwent neuropsychological evaluation, mobility assessment, and structural brain neuroimaging. Linear regression was conducted with predictors including gray matter volume in six regions of interest and white matter hyperintensity burden, with mobility measures as outcomes. RESULTS: Lower gray matter volume in caudate nucleus was associated with slower speed on a functional mobility task. Higher cerebellar volume was also associated with slower functional mobility. White matter hyperintensity burden was not significantly associated with mobility. CONCLUSION: Our findings provide evidence for associations between subcortical gray matter volume and speed on a functional mobility task among cognitively impaired individuals. □